Significance of Pelvic Floor Hiatus in Female Pelvic Organ Prolapse - Jenn-Ming Yang; Wen-Chen Huang (Journal of Medical Ultrasound)
Pelvic floor hiatus (PFH) is the pelvic floor passage through which the pelvic organs pass. Proper PFH closure is essential to maintaining normal pelvic organ support. PFH can be explored with urogenital hiatus or levator hiatus, according to different anatomical definitions. Factors affecting PFH include age, ethnicity, body mass index, levator ani muscle integrity, resting tone, and contraction force of pelvic floor muscle. The ineffectiveness of PFH to stay adequately closed is not only associated with pelvic floor disorders including pelvic organ prolapse (POP) but also accountable for recurrent POP after pelvic floor repairs. Advancing our comprehension of the mechanism of an enlarged PFH and how PFH enlargement affects pelvic floor support would promote better prevention strategies and improved treatments.